Villages SDG's response to mental health: Better late than never - Sijabat, Saut Gracer (Journal of Social, Humanity, and Education, 2024)
Purpose: This article presents village-based mental health policies in response to sustainable development goals. Research methodology: A qualitative research approach was used in conjunction with library research. Results: According to the findings of this study, the focus of development goals, namely living a healthy and affluent life, has not been on mental health. Furthermore, there are findings on advocacy, research and innovation, partnership, and integration of mental health and other SDGs. Contribution: Based on the findings of this study, several recommendations were made, including developing wise mental health policies in rural areas, increasing mental health commitments and budgets, mobilizing communities to respond to rural mental health policies, and improving treatment facilities and mental health response services. Novelty: Although the goals of sustainable development place a special emphasis on healthy and prosperous lives, insufficient data on mental health have been collected, and mental health policies based on village wisdom have not become a theme that many central and regional governments have implemented.